Relating Social Media Diffusion, Education Level and Cybersecurity Protection Mechanisms to E-Participation Initiatives: Insights from a Cross-Country Analysis - Ahangama, Supunmali (Information systems frontiers, 2023)
Virtual Social Networks (VSN) act as a catalyst for the success of the active participation of citizens in information sharing, collaboration, and decision making. VSN based e-participation tools allow many-to-many communication and collaboration near real-time with users who might be in geographically dispersed locations. It provides a platform to voice opinions and perspectives and share them with others in new and innovative ways. Cybersecurity is a key area that needs to be considered for the success and continuous use of e-participation systems as it protects user privacy and helps to avoid scams, harassment, and misinformation. The intervening effect of cybersecurity protection mechanisms and citizens’ education level on the relationship between VSN diffusion and e-participation initiatives is explored in the proposed research model presented in this paper. Moreover, this research model is explored for different stages of e-participation (e-information, e-consultation, and e-decision making) and the five dimensions of cybersecurity (legal, technical, organizational, capacity building, and cooperation). The findings indicate that improved VSN usage has increased e-participation (especially in e-consultation and e-decision making) as a result of improved cybersecurity protection and public education, highlighting the varying importance of different cybersecurity protection measures for three stages of e-participation. Thus, considering the recent problems like platform manipulation, misinformation and data breaches associated with the use of VSN for e-participation, this study emphasizes the importance of regulations, policies, partnerships, technical frameworks, and research to ensure cybersecurity, as well as the importance of education to enable the public to interact productively in e-participation activities. This study is performed using publicly available data from 115 countries and the research model is developed, drawing theoretical basis from the Protection Motivation Theory, Structuration Theory, and Endogenous Growth Theory. This paper recognizes the theoretical and practical implications, and limitations while recommending future research directions.